What we will do versus what we can do: The relative effects of unit‐level NPD motivation and capability - Zhao, Zheng Jane; Chadwick, Clint (Strategic Management Journal, 2014)
Although a firm's innovation performance has been commonly attributed to its innovative capability, in a study of 102 Chinese automobile assemblers, we find that employees' collective motivation for new product development ( NPD ) is more important than NPD capability in determining firms' innovation performance. This finding suggests that researchers need to simultaneously consider both unit‐level capability and unit‐level motivation in studying the mechanisms that drive innovation. Furthermore, our results indicate that a firm's strategic orientation focusing on NPD affects its employees' collective NPD motivation and NPD capability through relevant, mediating HRM practices . Copyright © 2013 John Wiley & Sons, Ltd.